The Influence of Achievement Motivation and Mathematical Resilience in Online Learning on Mathematics Learning Achievement - Chairuddin, Chairuddin; Arhita, Siska; Farman (Tarbawi : Jurnal Ilmu Pendidikan, 2024)
This research was motivated by the desire to see: (1) the influence of achievement motivation and mathematical resilience in online learning on mathematics learning achievement, (2) The influence of achievement motivation in online learning on mathematics learning achievement, (3) The influence of mathematical resilience in online learning on mathematics learning achievement. This research is quantitative and employs an ex-post facto design. The population in this study was all 344 class VII students at MTs Negeri 1 Kolaka. Sampling using a proportional random sampling technique obtained a sample of 44 students. Data collection methods included questionnaires and documentation. Data analysis uses multiple linear regression analysis. The research results show: (1) Fcount = 24.31970 ≥ Ftable = 3.220, which means that there is a positive and significant influence of achievement motivation and mathematical resilience in online learning on mathematics learning achievement; (2) tcount = 4.333 > ttable = 2.01954, which means that there is a positive and significant influence of achievement motivation in online learning on mathematics learning achievement; (3) tcount = 4.989 > ttable = 2.01954, which means that there is a positive and significant influence of mathematical resilience in online learning on mathematics learning achievement.